O “Anticristo” em Nietzsche: do signo ao livro de 1888 - Lopes, Kassio F. P (2023)
In this thesis, we gather and make explicit appointments related to the sign of the "Antichrist". in the philosophical corpus elaborated in the course of Nietzsche, unveiling the various uses e. meanings. Interpreted as metaphor, simple linguistic artifice or religious term. used polemically, the sign of the "Antichrist" appears often emptied of. content in the sphere of Nietzschean research. Here, however, we take seriously the uses e. senses of the anti-Christian figure in Nietzsche’s philosophy. However, our ultimate goal does not. restricted to the study of the sign, since we seek to enable an understanding. more accurate of the 1888 writing, entitled precisely The Antichrist, interrogating. especially what its place in the general scope of the literary and philosophical project that. Nietzsche had been elaborating in recent years in the socalled "Transvaluation of all. the values". Since the writing The Antichrist is considered as the most significant use of the sign, we cover and map in this research the entire route: from the figure to the book of 1888, which implied the task of analyzing, patient and carefully, the sign of the "Antichrist" polyphonic in the complex semiotic network of Nietzsche. Therefore, throughout the research we distinguish or need the meanings, perspectives or notions that lie in the use of this sign open and fleeting and depend contextually on the time in which he wrote and the text or writing in which the said figure is inserted. Through the investigation of the sign, we perceive a group or chain of references, indications and meanings from which to interpret The Antichrist of 1888 and, at the same time, describe the symbolic powers of this figure and the possible philosophical contents launched in the future